Acute portal vein thrombosis in an isolated, blunt, minor liver injury near the porta hepatis - Onchuda Wongweerakit; Osaree Akaraborworn; Burapat Sangthong; Komet Thongkhao (Chinese Journal of Traumatology)
Portal vein thrombosis (PVT) secondary to blunt abdominal trauma associated with liver injury is extremely rare in healthy individuals as well as in minor liver injury, and it carries a high rate of morbidity and mortality. Moreover, acute asymptomatic PVT is difficult to diagnose. We present a young trauma patient with isolated minor liver injury associated with acute PVT. A 27-year-old man presented to the emergency department after a motor vehicle collision. His primary survey findings were unremarkable. His secondary survey showed a large contusion (7 × 7 cm2) at the epigastrium with marked tenderness and localized guarding. The CT angiography of the whole abdomen revealed liver injury grade 3 in hepatic segments 2/3 and 4b (according to the American Association for the Surgery of Trauma classification) extending near the porta hepatis with patent hepatic and portal veins and without other solid organ injury. The follow-up CT of the whole abdomen on post-injury day 7 showed a 1.8-cm thrombus in the left portal vein with patent right portal and hepatic veins, and a decreased size of the hepatic lacerations. A liver function test was repeated on post-injury day 4, and it revealed improved transaminitis. The patient received intravenous anticoagulant therapy with low-molecular-weight heparin according to weight-based dosing for treatment. The CT of the whole abdomen performed 2 weeks after anticoagulant therapy showed small residual thrombosis in the left portal vein. The patient received intravenous anticoagulant therapy for a total of 3 months. On the follow-up visits at 1 month, 2 months, 6 months, and 1 year after the injury, the patients did not have any detectable abnormal symptoms. PVT post-blunt minor liver injury is an extremely rare complication. If the thrombosis is left untreated, serious morbidity and mortality can ensue. However, its diagnosis in asymptomatic patients is still challenging. Periodic imaging is necessary for highly suspected PVT, especially in liver injury with lacerations close to the porta hepatis, even in cases of a minor injury.